2013
DOI: 10.1021/ac400351c
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Determination of Nanomolar Cyanate Concentrations in Estuarine and Sea Waters by Precolumn Fluorescence Derivatization

Abstract: Recent studies suggest that cyanate (OCN(-)) is a potentially important source of reduced nitrogen (N) available to support the growth of aquatic microbes and, thus, may play a role in aquatic N cycling. However, aquatic OCN(-) distributions have not been previously described because of the lack of a suitable assay for measuring OCN(-) concentrations in natural waters. Previous methods were designed to quantify OCN(-) in aqueous samples with much higher reduced N concentrations (micromolar levels) than those l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…For example, while ammonium is frequently at the limit of analytical detection in surface waters, as was observed in this and other studies, it typically accounts for a large fraction of total N uptake because its production and consumption are tightly coupled (Bronk and Steinberg ; Mulholland and Lomas ). Cyanate concentrations were 1–2 orders of magnitude lower in coastal waters in the mid‐Atlantic than those previously observed from the Chesapeake Bay estuary (17–100 nM; Widner et al , unpubl.) and higher on the continental shelf than on the slope (Table ; Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For example, while ammonium is frequently at the limit of analytical detection in surface waters, as was observed in this and other studies, it typically accounts for a large fraction of total N uptake because its production and consumption are tightly coupled (Bronk and Steinberg ; Mulholland and Lomas ). Cyanate concentrations were 1–2 orders of magnitude lower in coastal waters in the mid‐Atlantic than those previously observed from the Chesapeake Bay estuary (17–100 nM; Widner et al , unpubl.) and higher on the continental shelf than on the slope (Table ; Fig.…”
Section: Discussionmentioning
confidence: 54%
“…However, marine cyanate concentrations had never been measured prior to the first three cruises, due to the lack of a cyanate assay for seawater, so we based our cyanate additions on those we used for ammonium, nitrite, nitrate, and urea uptake experiments (100 nM final concentration; Mulholland et al unpubl.). Prior to the August 2012 cruise, we made the first measurements of cyanate along a Chesapeake Bay mouth transect and found that cyanate concentrations there ranged from 27.3 nM to 41.1 nM (Widner et al ). Consequently, on the final cruise, tracer additions were decreased to 30 nM to minimize potential over‐estimation of rates while ensuring sufficient tracer to detect enrichment in the particulate phase and minimize depletion of the source pool over the course of the incubation (Lipschultz ).…”
Section: Methodsmentioning
confidence: 99%
“…Limits of detection for NO3, NO2, NH4+, and urea were 70 nM, 20 nM, 40 nM, and 80 nM, respectively, using the nutrient autoanalyzers, and the limit of detection for NH4+ using the OPA method was 10 nM. The limit of detection for cyanate was 0.4 nM (Widner et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Cyanate could result from equilibrium with intracellular urea or carbamoyl phosphate decomposition, and is a toxic N-containing compound existing in the ocean (Widner et al, 2013). The assembled unigene of cynS contained DinoSL at 5 0 end and almost complete coding region, indicating that it was dinoflagellate originated and was likely functional.…”
Section: N Uptake and Assimilationmentioning
confidence: 99%